# 1. h(x)=3

-x-2

what is the answer?

Answers: 1

## Answers

1. h(x)=3-x-2what is the answer? ...

-x-2

what is the answer?

Answers: 1

1. h(x)=3-x-2what is the answer? ...

answer:

the answer is -5

step-by-step explanation:

for an instance you lost 3 fingers of your one hand only to lose the other two then you won't have any finger in one hand therefore you have 5 less (-5) fingers. charot

2x²

Step-by-step explanation:

because 2+ (x+x) ² +2 (x+x)=2 so its 2x²

3x²-x-2 is a quadratic expression with a > 1

Step-by-step explanation:

F-x²

O- -2x

I - 1x

L- -2

-2x+1x= -(1)x

X²-x-2

hahaaoqpqowkwjnwnsneke